Comparison of the efficacy of denosumab and bisphosphonates for treating secondary osteoporosis in patients with rheumatoid arthritis. Issue 4 (4th July 2017) - Kinoshita, Hayato; Miyakoshi, Naohisa; Kashiwagura, Tsuyoshi; Kasukawa, Yuji; Sugimura, Yusuke; Shimada, Yoichi
Abstract: Objectives : This study aimed to investigate the efficacy of denosumab (compared with that of bisphosphonates) for preventing secondary osteoporosis and inflammation caused by excessive bone resorption in Japanese rheumatoid arthritis (RA) patients never previously treated for osteoporosis. Methods : Ninety-eight patients with coexisting RA and osteoporosis were enrolled. The patients were subdivided by whether they were treated with denosumab ( n = 49) or traditional bisphosphonates ( n = 49). RA disease activity, bone turnover markers, and bone mineral density (BMD) were compared between the two groups before treatment, and after 6 and 12 months of treatment. Results : There was no significant difference between the groups in any of the disease activity indices and BMD at any of the measured time points. With regard to bone metabolism, denosumab significantly reduced bone-specific alkaline phosphatase at 6 and 12 months compared with pretreatment, but had no effect on tartrate-resistant acid phosphatase 5b levels, suggesting an effect on the bone formation rate, but not on the bone resorption rate. Conclusions : Neither denosumab nor bisphosphonates could suppress inflammation or RA disease activity, but denosumab significantly suppressed a marker of bone metabolism in Japanese RA patients never previously treated for osteoporosis.